Faktor Prediktif Rekurensi Dini Adenokarsinoma Pankreas Setelah Bedah Reseksi Kuratif: Systematic Review - Soelaeman, Muhammad Faza; Rahmat, Favian Ariiq; Wardhana, Aji Wahyu (Cermin Dunia Kedokteran, 2024)
Introduction: Pancreatic adenocarcinoma stands as one of the most devastating forms of cancer, with a survival rate of less than 5% after 5 years. Despite resection surgery being the only curative option, recurrence occurs in up to 85% of cases. It is crucial to identify factors that can accurately predict the probability of recurrence for more effective management strategies. Method: Following the PRISMA guidelines, a systematic review was carried out by extracting relevant studies from the PubMed MEDLINE database. Results: A total of 1,345 studies were initially identified, and 34 studies were analyzed. A total of thirty-five predictive factors were identified and classified into preoperative and postoperative categories. These factors were be further subdivided into patient characteristics, biomarkers, tumor characteristics, and genetics. The most frequently observed factors were lymph node metastasis, serum CA 19-9 level, and tumor size. Conclusion: Preoperative and postoperative patient characteristics, genetics, biomarkers, and tumor characteristics data can be utilized to predict and implement suitable follow-up strategies aimed at enhancing patient survival rates.